The Effectiveness of Family Support on Drug Compliance in Type II DM Patients In RSU Mitra Medika Medan 2022 - Muharani Syaftriani, Afina; Kaban, Ani Rahmadhani; Mulidan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Type II DM is a disease with special symptoms, namely hyperglycemia. Poor adherence to medication is problematic when managing DM. An aspect that can improve medication discipline in Type II DM sufferers is family support. The family is a component that influences Type II DM sufferers in supporting patients to fulfill their medication. The research aims to assess the effectiveness of family support for medication discipline in Type II DM sufferers at Mitra Medika RSU. This research method uses an analytical survey with a cross sectional approach. The population in this study were all Type II DM patients in the internal medicine ward at Mitra Medika RSU in 2022 with a total of 308 patients. Samples were taken using a side purposive technique of 75 respondents. This study used a questionnaire instrument on family support and medication adherence for Type II DM patients. This study used a questionnaire instrument on family support and medication adherence in Type II DM patients. Based on analysis using the chi-square test, the p-value = 0.000 (<0.05). The conclusion was drawn that there is a significant relationship between family support and medication adherence in Type II DM patients at Mitra Medika General Hospital in 2022. It is hoped that families of Type II DM patients will maximize family support for treatment for family members who experience Type II DM.